Seven wonders of the solar system - Aguilar, David A. (Viking, 2017)
Presents detailed information and illustrations on seven locations in our solar system such as Mars, Titan, Saturn's Rings, and Europa. Features a DIY project to build a model of Olympus Mons--the biggest volcano in the solar system--and print and digital resources for further study.